Syngas production through steam and CO2 reforming of methane over Ni-based catalyst-A Review - Abdulwahid, Arman; Hagos, F. Y.; Abdul Adam, Abdullah; R., Mamat; Abd Rashid, Abd Aziz; Cheng, C. K. (IOP Publishing, 2020)
CH4 and CO2 are the two foremost greenhouse gases which are accountable for global warming. Controlling of their emissions and proper utilization has become significant challenge in the field of energy researches. Reforming of CH4 with steam and CO2 is one of the feasible solutions to convert the primary sources of greenhouse gases into syngas. Nowadays, syngas is an essential resource for many industrial applications to produce beneficial value-added products. Besides, it has been referred to as a transition from the fossil fuel towards pure hydrogen energy in the stationary internal combustion engines. Methane reforming with steam or CO2 occurs as a result of the reaction between methane and steam or CO2 in the presence of a catalyst at high temperature. Reaction routes need to be controlled to achieve the desired outputs. To control the reaction path, there are several parameters need to be technically optimized. Reaction kinetic is also necessary to find the reaction rate and select the convenience type of catalyst that can enhance the reaction rate. Catalyst selection and preparation are essential in the reaction because they contribute to the reaction outputs mainly of the syngas ratio (H2/CO). This manuscript is intended to observe the trend of technology improvements on thermodynamic analysis and kinetic study of steam and CO2 reforming of methane reactions over the Ni-based catalyst. It also presents the evaluation of the catalytic effect/properties and their relationship with the performance of the catalyst needed for the design and suitable for steam and dry reforming of methane reactions.